Genotype selection influences the quality of gluten-free bread from maize. (May 2020) - Ekpa, Onu; Palacios-Rojas, Natalia; Rosales, Aldo; Renzetti, Stefano; Fogliano, Vincenzo; Linnemann, Anita R.
Abstract: Making bread from maize is a technological challenge due to the poor viscoelastic properties of the dough. Maize germplasm as well as the thermoalkaline processing technique commonly used in Mexico can be harnessed for bread making purposes. We assessed the bread making performance of two maize hybrids, two landraces, and their thermoalkaline processed flour in addition to their blend with high zinc wheat. Significant differences ( P ≤ 0.05 ) were found in physical kernel characteristics such as flotation index, hardness, size and weight. Doughs had a higher consistency, springiness and gumminess than the untreated reference. Landrace L1 (Jala) had a larger specific volume (1.99 mL/g), softer texture (13.10 N) and faster springiness (0.90) but a relatively high staling (1.60), while landrace L2 (Cacahuacintle) and hybrid H1 (CSTH19001) had a lower staling (<0.50). The specific volume and softness of bread reduced in all thermoalkaline processed flours. Genotypes demonstrated significantly different performances during bread making, indicating that the choice of maize genotype significantly affected the final product. Thermoalkaline processed flour did not seem to improve bread quality, hence its application in bread making requires further study. Highlights: Significant differences were found in physical kernel characteristics. Differences in dough rheology and bread making quality exist among genotypes. Resistant starch is produced during thermoalkaline processing of maize. Thermoalkaline processing lowered enthalpy of all genotypes.